Analisis Pengaruh E - Service Quality, E - Logistic, dan E - Customer Relationship Manajemen Terhadap Kepuasan Konsumen Marketplace Shopee - Sabila, Agnes (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2021)
As one of the largest e-commerce markets in Southeast Asia, it is not surprising that Indonesia is flooded with several e-commerce companies that continue to innovate to dominate the market. One of the most popular and reputable e-commerce marketplace applications in Indonesia is Shopee. Based on the data collected, it was stated that in the 2020 trimester, Shopee was ranked first with up to 96.5 million visitors. In addition, Shopee is also ranked first in the AppStore and PlayStore as a marketplace that is widely downloaded as an application for shopping. This increase in Shopee marketplace visitors is based on consumer or customer satisfaction provided by the Shopee marketplace. The purpose of this research is to determine consumer satisfaction with Marketplce Shopee, using the variables E - Service Quality, E - Logistics and E - Customer Relationship Management.                The method used is descriptive quantitative with a population of students and students of level 4 UNP Kediri, and the sample is 50 respondents, namely students and students of level 4 management of UNP Kediri.                The results of the study show that simultaneously E - Service Quality (X1), E - Logistics (X2), and E - CRM (X3) have a significant effect on customer satisfaction (Y). It can be said that simultaneously E - Service Quality, E - Logistics, and E - CRM have a significant effect on customer satisfaction, 56% can be explained by the influence of the variables E - Service Quality, E - Logistics, and E - CRM. While 44% is influenced by other variables that are not studied or not included in this study.